A Correlative Study to Assess the Knowledge and Practice of Housewives Regarding Householdwaste Management in Selected Rural Community at Mangalore with a View to Provide an Information Pamphlet (Medico Legal Update, 2020)
Background: Improper waste management deteriorates public health, degrades quality of life, and polluteslocal air, water and land resources. It also causes global warming and climate change and impacts theentire planet. Environmental problem faced by communities living near garbage dumps and marshy landsinclude air pollution, fires, smoke, flooding etc. Long term health problems like asthma, bronchitis, hepatitis,jaundice, malaria, elephantiasis and typhoid too have been faced by communities. So waste which areconsidered to be hazardous need to be disposed off safely and adequately.Materials and Method: A descriptive correlative research design was used for this study. The samplecomprised of 60 housewives between 18-55 years of age. The sample was drawn through purposive samplingtechnique. The study was carried out in rural community at Mangalore. A structured knowledge questionnairewas used to determine the knowledge of the subjects and practice rating scale was administered to assess thepractice scores of housewives regarding household waste management.Results: Majority of the subjects (65%) were having only average knowledge with knowledge score rangingbetween 0-20 with median 18 and SD 3.01 and majority of the subjects were have moderate practice scoreon waste management with median 20 and SD 3.52. There was a significant relationship between knowledgescore and practice score of the subjects on waste management (r=0.346, df=59.000, p